2016
DOI: 10.4137/cmamd.s38092
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Serum Uric Acid may be Related to Methotrexate Efficacy in Early Rheumatoid Arthritis: Data from the Canadian Early Arthritis Cohort (CATCH)

Abstract: OBJECTIVESThe mechanism of action of methotrexate in rheumatoid arthritis (RA) is complex. It may increase adenosine levels by blocking its conversion to uric acid (UA). This study was done to determine if methotrexate lowers UA in early RA (ERA).METHODSData were obtained from Canadian Early Arthritis Cohort, an incident ERA cohort. All ERA patients with serial UA measurements were included, comparing those with methotrexate use vs. no methotrexate exposure (controls). Analyses were exploratory. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…This may be due to changes in adenosine levels, which is a key mechanism of anti-inflammatory effects. Increased adenosine levels, theoretically, result from decreased xanthine and uric acid synthesis [ 37 ]. It is also a strong proatherogenic factor, especially in a sustained concentration above 4 mg/dl [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to changes in adenosine levels, which is a key mechanism of anti-inflammatory effects. Increased adenosine levels, theoretically, result from decreased xanthine and uric acid synthesis [ 37 ]. It is also a strong proatherogenic factor, especially in a sustained concentration above 4 mg/dl [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired antioxidant status in the RA group may be related to the loss of antioxidant components due to the neutralisation of radicals produced as a consequence of inflammation in the joints involved, and this may be also caused by an inadequate supply of antioxidant nutrients [ 36 , 37 ]. Depletion of the antioxidant pool in RA may be also a consequence of therapy [ 38 ]. In the studied RA group, an inverse correlation of TAS with disease duration and number of swollen joints was shown.…”
Section: Discussionmentioning
confidence: 99%
“…A strong relationship between TAS values and the concentration of uric acid levels in healthy subjects, as well as populations with different chronic diseases, has been previously shown in several studies [ 20 , 41 ]. More than half of the RA group were treated with methotrexate, which could affect the level of uric acid and hence deplete the pool of low-molecular-weight antioxidants in serum [ 38 ]. The uric acid determination performed in our study, however, did not reveal significant differences between groups ( p = 0.062).…”
Section: Discussionmentioning
confidence: 99%
“…[8] Moreover, MTX and LEF are commonly taken by patients with RA that reduce uric acid levels also. [9,10] A recent study has demonstrated coexistence of RA and gout are not uncommon. [1113] However, a study by Petsch et al claimed incidence of gout with patients with RA do exist but is lower than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the patient's serum uric acid level was slightly raised. It may be due to: Female patients have estrogen and progesterone which can promote the elimination of uric acid such that it can maintain the normal uric acid levels; as our patient was on MTX and LEF for the treatment of RA, it is possible that MTX can inhibit synthesis of purine and increase the level of adenosine, [9] and LEF can increase the elimination of uric acid by reducing the levels of uric acid through regulation of urate transporter in renal epithelial cells [10] ; and RF is likely to prevent the deposition of uric acid crystals. Hence, for these reasons, the level of uric acid presents to be slightly higher, or even normal.…”
Section: Discussionmentioning
confidence: 99%